Trả lời:
( x + 2 )3 + ( x - 2 )3 - 2x ( x2 + 10 )
= x3 + 6x2 + 12x + 8 + x3 - 6x2 + 12x - 8 - 2x3 - 20x
= 4x
bài mình sai rồi, do mình hấp tấp quá, bài bạn @Quỳnh Anh đr bạn kham khảo bài bạn ấy nhé
\(\left(x+2\right)^3+\left(x-2\right)^3-2x\left(x^2+10\right)\)
\(=\left(x+2+x-2\right)\left[\left(x+2\right)^2+\left(x+2\right)\left(x-2\right)-\left(x-2\right)^2\right]-2x^3-20x\)
\(=2x\left(x^2+4x+4+x^2-4-x^2+4x-4\right)-2x^3-20x\)
\(=2x\left(x^2+8x-4\right)-2x^3-20x=2x^3+16x^2-8x-2x^3-20x\)
\(=16x^2-28x\)